Construction of a colorimetric sensor array based on the coupling reaction to identify phenols. Issue 9 (16th February 2022) - Zhong, Haotian; Xue, Yuting; Liu, Bin; Chen, Zhengbo; Li, Kai; Zuo, Xia
Abstract : We report a colorimetric sensor array, which uses two nanozymes as electronic tongues for fingerprint identification of six phenols. The six phenols at 50 nM have their own response patterns. The sensor array had distinguished the six phenols in actual samples successfully. Abstract : Phenols are harmful to the human body and the environment. Since there are a variety of phenols in actual samples, this requires a sensor which possesses the ability to simultaneously distinguish them. Herein, we report a colorimetric sensor array, which uses two nanozymes (Fe–N–C nanozymes and Cu–N–C nanozymes) as electronic tongues for fingerprint identification of six phenols (2, 4, 6-trichlorophenol (2, 4, 6-Tri), 4-nitrophenol (P-np), phenol (Phe), 3-chlorophenol (3-CP), 4-chlorophenol (4-CP), and o -nitrophenol ( O -np)) in the environment. Nanozymes catalyzed the reaction of hydrogen peroxide, different phenols and 4-aminoantipyrine (4-AAP) to produce different color variations. These signal changes as fingerprints encouraged us to develop a pattern recognition method for the identification of phenols by linear discriminant analysis (LDA). The six phenols at 50 nM have their own response patterns, respectively. Surprisingly, this sensor array had distinguished the six phenols in actual samples successfully.